Mapping Stakeholder Kawasan Konservasi Taman Pesisir Pantai Penyu Pangumbahan, Sukabumi - Siti Fauzia Rochmah; Indra Gumay Febryano; Hari Kaskoyo; Endang Linirin Widiastuti; Rahmat Safe’i; Novita Tresiana (Journal of Tropical Marine Science, 2022)
The existence of various stakeholders involved in the management of the conservation area is very important for the sustainability of the Pangumbahan Turtle Coastal Park conservation area. The purpose of this study is to map the stakeholders involved in efforts to protect conservation areas as protected areas and their roles. This study uses descriptive analysis through joint interviews with the stakeholders involved. The results obtained are, where DKP West Java, DKP Branch for the Southern Region of West Java, and the Pangumbahan Beach Turtle Park Service Unit as players where these stakeholders have very strong interests as well as influence or can be called the main actors; KKP, KLHK, Central Government, West Java Provincial Government, Pokmaswas Genteng Nusantara, Sukabumi Turtle Conservation Group, Pokdarwis Ekopatih, PT. Perfect South, PT. Indonesia Power, Ciracap Police, and Educational Institutions as contest setters because they have great influence but low interest; West Java Tourism Office, egg thieves, ojek tourism groups, fishermen, and Pelabuhanratu Unesco Global Geopark (CPUGG) as subjects because they have high importance but do not have strong influence; while the West Java Forestry Service, the Pangumbahan Village Government and the Ciracap District Government as crowds because they have weak interests and influence. The interests and influences of these stakeholders have a real influence on the protection policy of the Pangumbahan Turtle Coastal Park. Every stakeholder involved must always evaluate the policies that have been implemented so that the management of the Pangumbahan Turtle Coastal Park conservation area can be sustainable.